Práticas de atendimento a DST nas farmácias do Distrito Federal, Brasil: um estudo de intervenção Assistance for customers with sexually transmitted diseases at pharmacies in the Federal District, Brazil: an intervention study - Janeth de Oliveira Silva Naves; Lia Lusitana Cardozo de Castro; Gislane Ferreira de Melo; Adriana Giavoni; Edgar Merchán-Hamann (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
Pesquisa para investigar práticas, características dos trabalhadores e avaliar efetividade de intervenção educativa foi desenvolvida em setenta farmácias de Brasília e Taguatinga, Brasil, distribuídas em dois grupos; metade das farmácias participou de treinamento sobre DST. Realizou-se 411 visitas de pesquisadores simulando sintomas de DST, que resultaram em: encaminhamento ao médico em cerca de 30% dos atendimentos; indicação de medicamentos em mais de 70% dos atendimentos, embora nas entrevistas apenas 16,4% afirmaram fazê-lo; nenhum tratamento indicado era adequado segundo abordagem sindrômica; recomendações preventivas e tratamento de parceiros foram pouco freqüentes; farmacêuticos recomendaram ida ao médico mais do que balconistas e estes indicaram medicamentos mais do que farmacêuticos. O conhecimento dos trabalhadores sobre DST foi considerado superficial. Após intervenção educativa nenhum dos indicadores apresentou melhora significativa em ambos os grupos. As constatações apontam a necessidade de regulamentação e de intervenção para divulgação de práticas educativas para controle de doenças como as DST e para o uso racional de medicamentos nas farmácias. A quantitative survey was conducted to analyze the type of assistance provided by pharmacy employees for cases of STDs. Simulated customer visits and interviews were conducted in 70 pharmacies in Brasilia and Taguatinga, Brazil, randomly assigned to two groups, one of which participated in educational activities on STDs. There were 411 simulated client visits to the pharmacies, with the following results: recommendation to seek medical care in 30% of cases, while in 70% of cases the pharmacy employees themselves recommended some drug treatment (although only 16.4% admitted to such practice). None of these suggested treatments was appropriate, based on the syndromic approach. Recommendations for prevention and treatment of partners were rare. Pharmacists recommended consulting a physician more frequently than attendants, and the latter recommended medicines more frequently than the former. Pharmacy workers had only superficial knowledge of STDs. After an educational intervention, none of the indicators showed a significant improvement in either group. The observations point to the need for regulation and intervention to publicize educational practices for the control of diseases like STDs and for the rational use of medicines in pharmacies.